Undersökning av självspridning av contortatallen i norra Sverige - Sjödin, Jonas (SLU/Dept. of Forest Ecology and Management, 2012)
Over the past 40 years 600 000 ha of lodgepole pine (Pinus contorta ssp. latifolia (Engelm.) Critchf.) has been planted in Sweden (280 000 ha on SCA's forest land alone which represents about 15% of the company's total forest land area). In the early 70's SCA situated a number of experimental stands in order to investigate different aspects of the exotic tree, primarily growth rate. To be able to compare the two species plots with scots pine (Pinus sylvestris L.), this species was also planted at the same time and under the same conditions. A number of questions should always be raised when exotic species are introduced in an ecosystem. Invasiveness, the pathogen situation and purely ethical issues should be discussed. One of the limiting factors of the lodgepole pine's invasiveness is its serotinous cones. Nevertheless has a certain self-spread still been shown to occur in the Swedish forest. The serotinous cones of the lodgepole pine are an evolutionary adaption to forest fire. In these cones it accumulates a great number of seeds in order to be released after the next fire. In addition to these cones there are a few cones that are able to spread the seed without heat. This makes the culture populations of lodgepole pine and their close environment is subjected to continuous exposure of viable seeds. The intention of this report is to investigate the potential of self-spread and establishment of P. contorta beyond the bounds of the cultural stands in northern Sweden. The establishment ability of the lodgepole pine is influenced by several habitat characteristics (such as vegetation, altitude, latitude, soil moisture). In the autumn of 2011 a field study was conducted with the intention of collecting suitable data in order to analyze these characteristics. The studies were carried out on 20 of SCA's trial facilities. These are located between 120-510 meters above sea level and in the range of 62° 12' N and 66° 11' N. Similar studies were carried out in 2000 and those results gave the opportunity to a comparison between 30 and 40-year old stands. On both occasions string inventory was used throughout the data collection. The same strings were investigated in 2011 as in 2000. The number of lodgepole pine, Scots pine and Norway spruce seedlings were recorded. Height, edge zone type, vegetation, etc. were noted. Whether the plants become established on disturbed or undisturbed soil was also recorded. For lodgepole pine measured distance to the nearest parent tree. The results show the great importance of disturbance for plant establishment. Only 14% of lodgepole pine seedlings that were found were on the ground that was not disturbed in any way. This compared with a Scots pine and Norway spruce: 38% and 54%. In 2000 the majority of plants were also found in disturbed areas, but with slightly less difference between the disturbed /undisturbed soil: 32% and 68%. The total number of lodgepole pine seedlings/ha was 98 st (62 of 2000). Divided into buffer zone and inside the stock, the result is: 165 pcs/ha of buffer zone (113 pcs/ha in 2000) and 32 pcs/ha within the population (11 pcs/ha in 2000). The number of lodgepole pine seedlings were lower than both Swedish pine and Norway spruce, except inside the stock where the same number of lodgepole pine seedlings as a Swedish pine found: 32 pcs/ha (2000: 11 lodgepole pine/ha and 127 Scots pine/ha). The number of Norway spruce seedlings was much higher: 649 Norway spruce/ha in 2011 and 833 years in 2000). The tendency was the same in the edge zones. It was also found a gradual decrease in the number of plants with distance from the nearest parent tree: at 20-25 m found only 3% of the self-scattered lodgepole pine seedlings. This was roughly the same result as 10 years earlier. The self-scattered lodgepole pine seedlings grew at an average distance from the nearest parent tree about 9.6 m (6.7 m in 2000) and the average height was 61 cm (62 cm in 2000). The average height of the stock was in the year 2011 134 cm and in the border zones 47 cm (Scots pine: 191 cm and 71 cm and Norway spruce: 73 cm and 78 cm). The results show a lack of ability for plants to establish themselves in undisturbed soil. Only 14% of lodgepole pine seedlings that were found in the study grew on undisturbed ground. In comparison both Scots pine and Norway spruce showed a somewhat different result: 38% respectively 54% were found on undisturbed ground. In the study from 2000 there were registered a slightly smaller difference in the number of seedlings between the disturbed / undisturbed soil: 32% and 68%. Furthermore, the quantity of plants was distinctively reduced with the distance from the nearest parent tree. Merely 3% of the self-spread lodgepole pine seedlings were found at a distance of 20-25 meters. The results were largely unchanged from the former study 10 years earlier. There was no association between latitude nor altitude and the ability for the seedlings to establish.